Analisis Konsumsi Bandwidth pada Komunikasi Address Resolution Protocol dalam Jaringan - I Gede Agus Surya Negara; Arifiana Satya Nastiti; Ridha Muldina Negara; Rohmat Tulloh (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
Telecommunication grows rapidly as the need of good quality network service increases. This is also followed by the increasing number of customers, and consequently the increasing number of connected devices in the communication and data networks. Each device in a network can recognize and communicate with each other using ARP MAC address translation mechanism which will consume a certain amount of network bandwidth, thus, will affect the quality of network services. This research analyze the consumption of network bandwidth due to MAC address translation mechanism against the number of devices connected to the network, using Spirent Test Center as the ARP traffic generator in the network. The result shows that bandwidth consumption increases as the number of connected devices increases. When the number reaches 20000 or more, bandwidth consumption increases significantly.